COMPARATIVE EVALUATION OF COMPLEX TREATMENT OF PERI-IMPLANTITIS AFTER DENTAL IMPLANTATION ACCORDING TO MICROBIOLOGICAL INDICATIONS - Shodiev Sadulla Samekhjanovich; Akhtamov Temur Shukhrat ugli; Arabov Abduvokhid Davronovich (Research Focus International Scientific Journal, 2024)
66 patients who underwent dental implantation were observed. The main group received ozone therapy locally. A bacteriological study was carried out. It was found that as a result of the proposed method of combined treatment, the contamination of inflamed periodontal areas significantly decreased, both quantitatively and qualitatively.